Rediscovery of the toadlet Brachycephalus bufonoides Miranda-Ribeiro, 1920 (Anura: Brachycephalidae) with osteological and acoustic descriptions - Folly, Manuella; Amaral, Lucas Coutinho; Carvalho-E-Silva, Sergio Potsch De; Pombal Jr., José P. (Zootaxa, 2020)
Brachycephalus bufonoides was described as a “variety” of B. ephippium based on two specimens which 90 years later was considered full species. Besides its brief original description, nothing else is known for this species. Herein we report the rediscovery of the pumpkin-toadlet Brachycephalus bufonoides from Nova Friburgo, State of Rio de Janeiro, the second most populous area within the Atlantic Forest in Brazil. A detailed osteological description of this species was also provided, including skull, hyolaryngeal skeleton and postcranium skeleton. The laryngeal skeleton of Brachycephalus genus was depicted for the first time. We conducted a molecular phylogenetic analysis of Brachycephalus using DNA sequences comprising two fragments of mitochondrial gene (16S). Both analysis with Bayesian inference and maximum parsimony supported the recognition of B. bufonoides as an exclusive lineage, allocated within the B. ephippium species group in B. vertebralis lineage. We improved the diagnosis and variation of the species, including more collected specimens, coloration in vivo and advertisement call description. Compared with its congeners, B. bufonoides has skin on head and dorsum with dermal hyperossification; skull with hyperossification of postorbital crests; a pair of hyperossified bulges about equidistant between postorbital crests; fourth presacral vertebra with transverse process hyperossified, ornamented and sacral diapophyses hyperossified, which can be seen externally (lineage of B. vertebralis sensu Condez et al. 2020); presence of dermal ossification as separated bulges of each vertebrae; general background color orange with different intensities of dark orange blotches on dorsum, including bordering of sacral region; absence of osteoderms and presence of warts on the dorsolateral surface of body; medium body size (SVL of adults: 12.0–14.5 mm for males and 14.7–16.3 mm for females; Table 1); rough dorsum; advertisement calls with 13 to 17 pulses; presence of pulse period modulation; and advertisement calls with notes longer than 0.2 s (0.22 to 0.31 s). Herein an important contribution for the taxonomy and systematics of this genus is provided, including a large amount of novel information for B. bufonoides from different sources (i.e., molecular, morphological variation, bioacoustic), allowing it to be included in future studies of species delimitation and relationships within Brachycephalus. Also, the discovery of this species reiterates the importance of Nova Friburgo for the conservation of the Atlantic Forest biodiversity.